Respuesta :

Answer:

The answer is ((5m^7)(r^6)(y^4)/8

When you divide a variable with an exponent by a variable with an exponent, you subtract the exponents. But you can only combine the exponents if the variable/base is the same(it's different for subtraction/addition).

For example:

[tex]\frac{x^5}{y^2}[/tex]   You can't simplify this because they have different variables (x and y)

[tex]\frac{x^5}{x^2} =x^{5-2}=x^3[/tex]     You can simplify since they have the same variable of x

When the exponent is negative, you have to move the variable and the exponent to the other side of the fraction to make the exponent positive.

For example:

[tex]\frac{x^2}{x^7}=x^{2-7}=x^{-5}=\frac{1}{x^5}[/tex]

[tex]\frac{y}{y^4}=y^{1-4} = y^{-3}=\frac{1}{y^3}[/tex]

You can do the problem like this:

[tex](\frac{-10}{-16} )(m^{-1+8})(y^{0+4})(r^{1+5})[/tex]   2 negative signs cancel out and becomes +

[tex](\frac{5}{8} )(m^7)(y^4)(r^6)[/tex]

Your answer is:

[tex]\frac{5m^7y^4r^6}{8}[/tex]